Influencing Factors for Sanitary Sewage in Brazilian Municipalities (Global Journal of Management and Business Research, 2024)
Summary- The objective of this work is to identify the main influential factors for the attendance of sanitary sewage in Brazilian municipalities through a survey and quantitative analysis of secondary data The justification is to contribute to a more systemic and integrated view of sanitary sewage services in the country and their potential causes linked to the context of infrastructure in the country The conceptual framework pre-establishes relationships between total sanitary sewage care and independent variables related to the availability of sustainable inputs technologies nature and quality of institutions human competences financing socio-environmental governance and sanitary administration The methodology adopted is quantitative research with random and stratified sampling of municipalities applying correlation analysis and multivariate regression The results of the research point to a positive correlation between the total sanitary sewage service and variables associated with the physical governmental structure and human relations existing in the health area
Keywords: sanitation; legislation; quantitative research